Search for low mass vector resonances decaying to quark-antiquark pairs in proton-proton collisions at s =13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Md. Ali, Mohd. Adli (American Physical Society, 2017)
A search is reported for a narrow vector resonance decaying to quark-antiquark pairs in proton-proton collisions at ffiffi s p ¼ 13 TeV, collected with the CMS detector at the LHC. The data sample corresponds to an integrated luminosity of 2.7 fb−1. The vector resonance is produced at large transverse momenta, with its decay products merged into a single jet. The resulting signature is a peak over background in the distribution of the invariant mass of the jet. The results are interpreted in the framework of a leptophobic vector resonance and no evidence is found for such particles in the mass range of 100–300 GeV. Upper limits at 95% confidence level on the production cross section are presented in a region of mass-coupling phase space previously unexplored at the LHC. The region below 140 GeV has not been explored by any previous experiments.